Public knowledge, attitude, and perception toward conventional and novel ocular treatment in Malaysia - Siti Nabilah Abdullah; Awis Sukarni Mohmad Sabere (Wolters Kluwer Medknow Publications, 2021)
One of the major concerns in any pharmacological treatment is the patients' adherence to medication. However, different types of ocular dosage forms might result in different response and compliance from the patients. This study investigated and compared public willingness on different types of dosage forms available for ocular treatment. The study also evaluated their willingness on new approach for the treatment based on their knowledge, attitude, and perception. This study was conducted between October and December 2017 through a set of questionnaires applied to 90 respondents between the age of 18 and 60 years who lived in Muar and Kuantan, Malaysia. The results were analyzed using SPSS software version 22.0 including inferential and descriptive statistics. There was no significant difference in the knowledge level between all age groups towards different types of dosage forms available; eye drops (P = 0.09), eye ointment (P = 0.252), medicated contact lens (P = 0.05), ocular mini-tablets (P = 0.06), and ocular inserts (P = 0.075). There is a variation of results among the public towards different types of dosage forms with their willingness to try conventional and novel approach. Eye drops show the highest willingness followed by eye ointment (less willingness). However, most of them showed no willingness towards medicated contact lens, ocular mini-tablets, and ocular insert. This research hopes to provide an overview on the development process of new formulation and dosage forms based on the patients' willingness level in an attempt to increase patient compliance.